Catwings return - Le Guin, Ursula K., 1929-; Schindler, S. D. (New York : Orchard Books, 1989)
Wishing to visit their mother, two winged cats leave their new country home to return to the city, where they discover a winged kitten in a building about to be demolished.
Booklist starred.
Horn Book.
4.8
3-6
Keywords: Cats -- Fiction; Fantasy; Fantasy fiction